Analisis Perbandingan Fonologi Bahasa Indonesia dan Bahasa Melayu dalam Kartun Upin Upin - Sintia Pratama; Irna Yanti; Erva Siti Nurchotimah (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This study aims to determine the comparison between Indonesian and Malay from a phonological aspect by using the cartoon series